Hubungan Status Gizi dan Aktivitas Fisik dengan Kejadian Dismenorea Primer pada Remaja Putri di SMPN 31 Banjarmasin - Krisneni Sibuea; Kristina Yuniarti; Yuliani Budiyarti; Ruslinawati Ruslinawati (Universitas Malahayati Lampung, 2025)
ABSTRACT The menstrual experience among adolescent girls varies; while some undergo menstruation without complaints, many experience primary dysmenorrhea, characterized by menstrual pain without underlying reproductive organ abnormalities. Contributing factors include undernutrition (underweight or severely underweight status) and low levels of physical activity. This study aimed to examine the relationship between nutritional status and physical activity with the incidence of primary dysmenorrhea among adolescent girls. A quantitative method with a cross-sectional approach was used. The study population consisted of 8th-grade female students (classes VIII A–E) at SMPN 31 Banjarmasin during the 2024/2025 academic year, with 67 participants selected through purposive sampling. Instruments included a body weight scale, height measuring tape, the Global Physical Activity Questionnaire (GPAQ), and a primary dysmenorrhea questionnaire. Data were analyzed using Spearman’s rho test. Results showed a significant relationship between nutritional status and the incidence of primary dysmenorrhea (p = 0.001; r = 0.410), and a very strong relationship between physical activity and the incidence of primary dysmenorrhea (p = 0.000; r = 0.821). It can be concluded that nutritional status and physical activity are significantly associated with primary dysmenorrhea among adolescent girls. These findings are expected to serve as a basis for health education to raise awareness about the importance of balanced nutrition and regular physical activity in reducing menstrual pain symptoms. Keywords: Primary Dysmenorrhea, Adolescent Girls, Nutritional Status, Physical Activity ABSTRAK Pengalaman menstruasi pada remaja putri berbeda-beda, sebagian mengalami tanpa keluhan, namun banyak pula yang merasakan dismenorea primer, yaitu nyeri menstruasi tanpa kelainan organ reproduksi. Faktor yang berkontribusi antara lain status gizi yang tidak ideal (kurus dan sangat kurus) dan aktivitas fisik yang rendah. Penelitian ini bertujuan untuk mengetahui hubungan antara status gizi dan aktivitas fisik dengan kejadian dismenorea primer pada remaja putri. Desain penelitian menggunakan metode kuantitatif dengan pendekatan cross-sectional. Populasi adalah siswi kelas VIII A–E SMPN 31 Banjarmasin tahun ajaran 2024/2025, dengan jumlah sampel 67 orang yang diambil menggunakan teknik purposive sampling. Instrumen penelitian meliputi timbangan berat badan, meteran tinggi badan, kuesioner Global Physical Activity Questionnaire (GPAQ), dan kuesioner kejadian dismenorea primer. Analisis data menggunakan uji Spearman’s rho. Hasil menunjukkan terdapat hubungan signifikan antara status gizi dengan kejadian dismenorea primer (p = 0,001; r = 0,410), serta hubungan yang sangat kuat antara aktivitas fisik dengan kejadian dismenorea primer (p = 0,000; r = 0,821). Disimpulkan bahwa status gizi dan aktivitas fisik memiliki hubungan bermakna dengan kejadian dismenorea primer pada remaja putri. Hasil ini diharapkan menjadi landasan edukasi untuk meningkatkan kesadaran akan pentingnya gizi seimbang dan aktivitas fisik dalam mengurangi keluhan menstruasi. Kata Kunci: Dismenorea Primer, Remaja Putri, Status Gizi, Aktivitas Fisik